VG Pasta Production / Nurul I'zzati Ramli... [et al.] - Ramli, Nurul I'zzati; Mohd Latfee, Fatin Syazwani; Abdul Razak, Farah Nadhirah; Mohd Noor, Madihah; Md Anuar, Nabilah Izzati; Zukifli, Zahraatul Aaina (2020)
We are making pasta from vegetables that has been steamed until become soft to start our business. We choosing to making this product because, in Malaysia there is a few company that produced the same products but using the different vegetables. Besides, nowadays people are more concern on healthy lifestyle and tend to eat the food that contains high amount of nutrients. The research show that vegetables has many benefit to human health and need to consume by the human every day.We produce pasta from carrots, beetroot and pumpkin. The price of vegetables pasta is based on the box that consists of IO packets. Every packet of vegetables pasta consists of 250 g of this pasta. The price of the box is RM 180.00 which RM 18.00 per packet. The price is medium compare to other regular pasta and it considered fine as our product contain vegetables which are on another level. The reason we put such medium price because we want people from rural and urban areas able to consume our product. We believe that our product can reach people heart, compete with our competitors soon and keep improving in the future.